RELIGIO-CENTRIC SELLING STRATEGY IN THE RELATIONSHIP BETWEEN MARKET SENSING CAPABILITIESAND THE SMEs BUSINESS PERFORMANCE - Hendar, Hendar (IJIBE (International Journal of Islamic Business Ethics), 2019)
This paper aims to investigate and examine the mediating role of religio-centric selling strategy in relation to market sensing capabilities with SMEs business performance in religious-based industries. This paper selected 330 Muslim SMEs in Central Java and tested the regressive relationships of the three constructs. Through confirmatory factor analysis and goodness of fit model testing using SEM, the results of market sensing capabilities obtained have a positive effect on the religio-centric selling strategy and SMEs business performance. In addition, the religio-centric selling strategy also has a positive impact on SMEs business performance. Therefore, the religio-centric selling strategy really acts as a partial mediation in relation to market sensing capabilities with SMEs business performance. By examining the literature on various marketing capabilities, selling strategies, religiosity, and SMEs business performance, this paper offers a unique analysis of the relationship between market sensing capabilities and religio-centric selling strategy and their impact on SMEs business performance. Conceptual discussions and empirical results are expected to extend previous research on the culture of market orientation and selling strategy in specific religious-based small businesses.